2023
DOI: 10.1002/ajim.23530
|View full text |Cite
|
Sign up to set email alerts
|

Underreporting of work‐related low back pain among registered nurses: A mixed method study

Suyoung Kwon,
Soo Jeong Lee

Abstract: BackgroundIdentifying and addressing work‐related health problems early is crucial, but workers often perceive barriers in reporting these to management. This study aimed to investigate the factors associated with nurses' reporting of work‐related low back pain to their managers and explored the reasons why nurses with patient handling injuries did not report them.MethodsThis study is a concurrent mixed‐method analysis of data from two statewide cross‐sectional surveys of California registered nurses conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…We agree with the authors and want to highlight how the NIOSH Health Hazard Evaluations (HHE) Program may contribute to reducing ergonomic injury among interventional pulmonologists. NIOSH ergonomic research has identified risk factors for musculoskeletal disorders and developed engineering controls and administrative recommendations that are applicable to a range of settings to reduce musculoskeletal disorders ( 1 , 2 ). Healthcare workers historically have faced high rates of occupational musculoskeletal disorders, such as back pain ( 2 , 3 ); therefore, safe patient handling has long been an emphasis of NIOSH and other healthcare-related professional societies ( 4 ).…”
mentioning
confidence: 99%
“…We agree with the authors and want to highlight how the NIOSH Health Hazard Evaluations (HHE) Program may contribute to reducing ergonomic injury among interventional pulmonologists. NIOSH ergonomic research has identified risk factors for musculoskeletal disorders and developed engineering controls and administrative recommendations that are applicable to a range of settings to reduce musculoskeletal disorders ( 1 , 2 ). Healthcare workers historically have faced high rates of occupational musculoskeletal disorders, such as back pain ( 2 , 3 ); therefore, safe patient handling has long been an emphasis of NIOSH and other healthcare-related professional societies ( 4 ).…”
mentioning
confidence: 99%